2010
DOI: 10.1108/02686901011008972
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of corporate internet reporting: evidence from Egypt

Abstract: Purpose -The purpose of this paper is to examine the potential factors that may affect the level of corporate internet reporting by Egyptian listed companies. Design/methodology/approach -The content analysis approach to examine the information cited by the largest Egyptian companies is used in their web sites. The paper modifies and uses the disclosure index of Xiao et al. Ordinary least square multiple regression analysis is used to examine the determinants of the internet reporting. Findings -It is found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
232
8
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(279 citation statements)
references
References 45 publications
24
232
8
15
Order By: Relevance
“…and empirical literature that suggests they can potentially affect voluntary CG disclosure (SCGI) (Abdelsalam & Street, 2007;Al-Janadi et al, 2013;Aly et al, 2010;Botosan, 1997;Y. Bozec & Bozec, 2007;Fifka, 2013;Hooghiemstra, 2012;Hussainey & Al-Najjar, 2012;Rouf, 2011;Samaha et al, 2012).…”
Section: Research Method: Definition Of Variables and Model Specificamentioning
confidence: 99%
See 1 more Smart Citation
“…and empirical literature that suggests they can potentially affect voluntary CG disclosure (SCGI) (Abdelsalam & Street, 2007;Al-Janadi et al, 2013;Aly et al, 2010;Botosan, 1997;Y. Bozec & Bozec, 2007;Fifka, 2013;Hooghiemstra, 2012;Hussainey & Al-Najjar, 2012;Rouf, 2011;Samaha et al, 2012).…”
Section: Research Method: Definition Of Variables and Model Specificamentioning
confidence: 99%
“…One way of determining external auditor quality is the level of disclosure, and in fact, audit firm size has been suggested to have a positive effect on corporate disclosure (Eng & Mak, 2003;Owusu-Ansah, 1998) and audit quality (DeAngelo, 1981). This is because larger audit firms have greater financial strength, experience, expertise, information, and knowledge (DeAngelo, 1981;Ntim, Opong, Danbolt, & Thomas, 2012), which can improve their independence and ability to limit opportunistic activities of managers (Alsaeed, 2006;Aly, Simon, & Hussainey, 2010).…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%
“…In risk reporting studies, Beretta andBozzolan (2004) andRajab andHandley-Schechter (2009) found that risk reporting differs among different industry sectors. Signalling theory suggests that firms in the same industry sector are more likely to adopt the same level of disclosure (Aly et al, 2010). If a company within an industry fails to follow the same disclosure practices as others in the same industry, then it may be interpreted as a signal of hiding bad news (Craven and Marston, 1999).…”
Section: Firm Characteristics and Crdmentioning
confidence: 99%
“…Each company's annual report was scanned for these items and measured using an un-weighted disclosure index. Aly et al (2010) noted that a majority of studies in this field have used an un-weighted disclosure index. Indeed, Cooke (1989a) has argued that un-weighted indices are a suitable research instruments in corporate disclosure studies when the research is focused on all groups who use a company's annual report rather than the requirements of any specific user category.…”
Section: Measurement Of Financial Instruments Disclosurementioning
confidence: 99%